Abstract 274: Mechanical Thrombectomy for Ischemic Stroke in Elderly Population - Kareem El Naamani; Divya Mudundi; Michael R. Gooch; Stavropoula I. Tjoumakaris; Robert H. Rosenwasser; Pascal Jabbour; Nabeel A. Herial (Stroke: Vascular and Interventional Neurology)
Introduction Stroke is a leading cause of mortality and morbidity worldwide and the risk increases with age. Mechanical thrombectomy (MT) in eligible patients is proven to improve outcomes and is ow standard of care for acute ischemic stroke. Clinical trials evaluating MT often exclude patients older than 80 and available scientific evidence supporting MT in elderly is limited and varied. Purpose of this systematic review is to examine current literature on efficacy and outcomes of MT in octogenarian and nonagenarian stroke patients. Methods A literature search was conducted using PubMed and Scopus from 2013‐2023. All studies that included patients 80 yrs and older with acute ischemic stroke who underwent MT and provided 90‐day clinical outcomes and rates of complications were reviewed. Results Review identified 25 publications and the median age of study populations ranged from 82 to 93.3 years with proportion of female patients higher in all studies. Success rate of MT ranged from 66.7% to 97%. Symptomatic intracranial hemorrhage was the common complication ranging from 3% to 28%. The 90‐day mortality rate ranged from 7% to 70%. No differences were noted between octogenarians and nonagenarians. Conclusion MT in elderly patients had high reperfusion rates indicating procedural success, and variable clinical outcomes with wide range of complication and mortality rates. Factors influencing MT outcomes in elderly are discussed and the need for randomized control trials providing the highest level of scientific evidence for MT in this population is emphasized.